2014
DOI: 10.1080/08946566.2014.883947
|View full text |Cite
|
Sign up to set email alerts
|

Note From Iran: Self-Reported Elder Abuse in Qazvin, 2012

Abstract: This brief report provides a first look at self-reported instances of elder abuse by a sample of people 60 years and older living in Qazvin, Iran. Six hundred community-dwelling persons, drawn from the registry files of each health center in Qazin, completed questionnaires during April to October 2012. At least 80% of the participants reported experiencing some form of psychological abuse, financial abuse, and/or neglect at least once during a 2-month period. Physical and sexual abuse were rarely reported. Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 4 publications
0
12
2
Order By: Relevance
“…The study of Li Wu, showed that the elderly people who live alone usually experience higher levels of abuse (28), and other studies indicated that being widowed can be considered as the high risk for experiencing abuse (39); this may result from the fact that cohabitation increases the risk of conflicts and contacts; therefore, the level of abuse may increase in contrast. In the current study, elderly men were at higher risk of abuse than women; while, in the studies of Li Wu, Garre, and Nowrouzi women had experienced higher abuse (28,40,41). This difference may result from different sampling methods, more men rather women in the population under study, or elderly women are more respectable and usually experience lower levels of abuse; since they do house hold responsibilities such as cooking or taking care of grandchildren.…”
Section: Discussioncontrasting
confidence: 38%
“…The study of Li Wu, showed that the elderly people who live alone usually experience higher levels of abuse (28), and other studies indicated that being widowed can be considered as the high risk for experiencing abuse (39); this may result from the fact that cohabitation increases the risk of conflicts and contacts; therefore, the level of abuse may increase in contrast. In the current study, elderly men were at higher risk of abuse than women; while, in the studies of Li Wu, Garre, and Nowrouzi women had experienced higher abuse (28,40,41). This difference may result from different sampling methods, more men rather women in the population under study, or elderly women are more respectable and usually experience lower levels of abuse; since they do house hold responsibilities such as cooking or taking care of grandchildren.…”
Section: Discussioncontrasting
confidence: 38%
“…The first step in preventing violence is to identify it through public health policies and programs. 30 The strong points of the present study include the population coverage and the representativeness of the sample. The limitations include the cross-sectional design, which did not favor the establishment of causality -such as knowing whether the elderly individual classified their health as poor/very poor or if an illness was present prior to the mistreatment.…”
Section: Discussionmentioning
confidence: 96%
“…If multiple family members met criteria, the member spending the most time with the elderly participant was preferred. Note that families were purposely not screened in based on EA, as the study is concerned with both primary and secondary intervention and prior work in these settings indicates high incidence of abuse (Abdi et al, 2019;Khanlary et al, 2016;Oveisi et al, 2014).…”
Section: Design and Proceduresmentioning
confidence: 99%
“…Iranian elderly are not exempt from EA (Khanlary et al, 2016;Oveisi et al, 2014), and prevalence rates have been estimated at 48.3% (Abdi et al, 2019). This is noteworthy given that Islam, a dominant religion in Iran, indicates that elders should be respected (Hosseinkhani et al, 2017).…”
Section: Introductionmentioning
confidence: 99%